Pengaruh Penggunaan Mulsa Terhadap Sifat Fisika Tanah Dan Kualitas Produksi Tanaman - Harefa, Ricardo Fondraradodo; Laia, Erniaman (CV. SINAR HOWUHOWU, 2024)
This study aims to analyze the effects of different types of mulch on soil physical properties, including moisture, temperature, and porosity, as well as on crop production quality. The experiment was conducted using a Randomized Block Design (RBD) with four treatments: no mulch (control), silver-black plastic mulch, rice straw mulch, and sawdust mulch. The results indicate that mulch usage significantly increased soil moisture and maintained a more stable temperature compared to the control. Silver-black plastic mulch increased soil temperature by 2–3°C, while organic mulches provided higher moisture retention and improved porosity. Furthermore, plant production quality, including plant height, branch count, and fruit yield, was better in the mulched treatments, especially with plastic mulch. Economic analysis suggests that organic mulch is more cost-effective in the long term and supports sustainable agricultural practices. Thus, mulch usage is an effective technique to improve soil quality and crop productivity.